Problemy dynamizacji w procesie ustalania benchmarku - Markowska, Małgorzata (The problem of dynamics in the process of benchmark setting, 2005)
The problem of dynamics refers, apart from modelling, also to other research aspects, including among others the choice of benchmark in regional research. The objective of the article is the presentation of possibilities for the use of arithmetic mean for benchmarking, including its recurring „modification”, classification methods and distance measurements. The approaches suggested within the scope of the study take into consideration the dynamic nature of discussed phenomena
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 227-238